Racial Literacy Is Literacy: Locating Racial Literacy in the College Composition Classroom - Mara Lee Grayson (Journal of the Assembly for Expanded Perspectives on Learning, 2019)
In order to develop pedagogies around racial literacy, we must first define the goals and bounds of racial literacy as praxis. In this paper, I synthesize the findings of a year-long teacher research project to explore the significance of racial literacy in the college composition classroom. Drawing from existing scholarship and my own research into racial literacy instruction, I offer four visions of racial literacy in the English classroom, the last of which is Racial Literacy as Literacy. I conclude by arguing that a racial literacy curriculum can teach students foundational concepts of textual analysis, audience awareness, authorial choice and positionality, and argumentation. In short, racial literacy is a culturally relevant, critical framework for literacy instruction.